Meningkatkan Hasil Belajar Kebugaran Jasmani Kekuatan Otot Perut Melalui Modifikasi Permainan Estafet Bola di Atas Kepala Untuk Siswa Kelas X-7 SMA Negeri 9 Malang: Penelitian - Arum Filsafat; Salamet; Winarno (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Physical Education, Sports, and Healthy at the high school level plays an important role in developing students' motor skills, particularly in the aspect of physical fitness such as abdominal muscle strength. This study aims to determine the effectiveness of a modified overhead ball relay game as a learning model to improve the abdominal muscle strength of tenth-grade students in class X-7 at SMAN 9 Malang. The study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 35 students, with data collected through physical fitness tests (sit-up assessments) and analyzed both quantitatively and qualitatively. Initial findings showed that most students were categorized as “low” in abdominal muscle strength. After implementing the modified overhead ball relay game, a significant improvement was observed: the success rate increased from 44.8% in the pre-test to 64.6% in the first cycle, and further to 76% in the second cycle. These results indicate that a game-based learning model not only enhances physical fitness but also boosts motivation, cooperation, and student enthusiasm during physical education sessions. Therefore, the modified overhead ball relay game can be considered an effective, enjoyable, and meaningful alternative strategy for improving students’ physical fitness, particularly in strengthening the abdominal muscles.